Serum and ascitic procalcitonin as a marker for early diagnosis of spontaneous bacterial peritonitis - Elsayed I Elshayeb; Mohamed H Badr; Eman M. Abdu Elgayed; Amira S Nor El-dean (SpringerOpen, 2019)
Background and aim of the work Spontaneous bacterial peritonitis (SBP) is a serious complication in patients with decompensated cirrhosis. SBP is an inflammation of the peritoneum by micro-organisms such as gram-negative bacilli. Early diagnosis of SBP is essential which may be a challenge for clinicians owing to lack of symptoms in early stage of SBP. The aim of this study is to evaluate procalcitonin (PCT) level in the serum and ascitic fluid of patients with cirrhosis for early diagnosis of SBP. Patients and methods This study was carried out on 45 patients with decompensated liver cirrhosis. They were classified into two groups: group 1 included 15 patients free of SBP and group 2 with SBP based on ascetic polymprphnuclear leucocytes (PNLs) more than 250/3 mm and ascitic fluid culture. Evaluation of C-reactive protein, ascetic fluid polymorphs count, and serum and ascetic PCT levels was done for all patients. Results No significant difference between SBP group and non-SBP group regarding ascetic PCT level, with P value more than 0.05. Serum PCT in patients with SBP shows high statistically significant difference, with P value less than 0.005, in comparison with patients without SBP. Conclusion Serum PCT is a good predictor marker for early diagnosis of SBP in patients with decompensated cirrhosis.